2013
DOI: 10.1123/pes.25.2.221
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of the Effect of Intra-Articular Corticosteroid Injection on Isokinetic Muscle Strength in Children With Juvenile Idiopathic Arthritis

Abstract: This study assessed the magnitude of changes in isokinetic muscle strength in children with juvenile idiopathic arthritis (JIA) before and after treatment with intra-articular corticosteroid injection and assessed the feasibility of a larger study of the same effect. Isokinetic dynamometry was used to measure peak knee extension and flexion torque in 12 children before and after treatment for unilateral knee arthritis. Extensor and flexor strength was reduced on the affected side before treatment (-0.56Nm/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In our study, children with JIA walked with reduced walking speed and decreased range of motion, predominantly in the sagittal plane. We did not measure muscle strength, but one could hypothesize that strength was diminished, as supported by the finding of reduced ankle power . In healthy children, reduced walking speed is associated with an increased ankle power to hip power ratio, indicating greater relative impact on the ankle .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, children with JIA walked with reduced walking speed and decreased range of motion, predominantly in the sagittal plane. We did not measure muscle strength, but one could hypothesize that strength was diminished, as supported by the finding of reduced ankle power . In healthy children, reduced walking speed is associated with an increased ankle power to hip power ratio, indicating greater relative impact on the ankle .…”
Section: Discussionmentioning
confidence: 98%
“…Lelieveld et al concluded that only 23% of children with JIA met public health recommendations to perform >1 hour daily moderate to vigorous physical activity, compared to 66% in a healthy reference group . Inflammation surrounding affected joints leads to muscular weakness, which may persist when the disease is inactive . Children with a history of ankle involvement demonstrate reduced ability to generate ankle power during push‐off in walking , which may impact participation in more demanding physical activities such as running and jumping.…”
Section: Introductionmentioning
confidence: 99%
“…In this study a lower dynamic joint function especially extension torque in arthritic knee joints compared to healthy was found. McKay demonstrated reduced knee extensor strength using isokinetic dynamometer in children with JIA and active arthritis [ 38 ]. Hedengren found lower joint torque values in a subgroup of children with arthritis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lanni et al found that treatment with IACIs in a considerable number of patients injected in single or multiple joints can induce sustained relief of synovitis and has good safety ( 39 ). McKay thought that the improvement of the strength of the extensor and flexor muscles was considered to be of clinical significance after active treatment of inflamed knee joints with IACIs ( 40 ). In 2010, Scott re-evaluated IACIs for children with JIA and confirmed that IACIs are a safe, rapid, and effective treatment method ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, after injecting corticosteroids into the joint cavity, an exercise program may be needed, and confirmation of persisting deficits in knee extensor strength indicates that specific intensive exercise or physical therapy should be carried out after IACIs to resolve the strength deficiency. This is not only to improve strength but also to improve function and solve biomechanical abnormalities in gait ( 40 ). In 2019, Elaine et al compared the group that was not splinted with the group that was splinted after IACI of the knee and concluded that the risk of recurrent arthritis was not statistically significant ( 48 ).…”
Section: Methodsmentioning
confidence: 99%